Cal Polytechnic School, Near San Luis Obispo Cal. 694 (1907)
Front elevations of Household Arts, Weeks Administration Building, and Dormitory; color printed.(Addressed to Miss Edith Bianchi, Cambria, signed 'Joe' (possibly Joseph Bianchi, Class of 1909); postmarked Sep. 1907; Edward H. Mitchell, Publisher, San Francisco, printed in the United States, no. 694)